Mensch und Meer: Zur sozialen Aneignung der Ozeane - Biermann, Frank (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
This essay cxplores the political economy of ocean space, i.e. the political process of appropriation and exploitation of the seas by human societies in the 20th century. The analysis focuses on two developments: the progrcssing acquisition of ocean space and marine resourccs by coastal states, and the establishment of a substantial body of legal rules governing the remaining freedom rights of states, in particular in the area of environmental protection and the safety of life at sea. A third important aspect of ocean politics is discussed in the final pmt of the essay: the growing disturbance, pmtly even destruction of marine ecosystems. The pollution of the marine environment has resulted in a paradigmatic shift in the relationship between human societies and the seas which necessitates fundamentally new approaches in the governance of ocean space.